Chapter Flow Based Enumeration of Plasmablasts in Peripheral Blood After Vaccination as a Novel Diagnostic Marker for Assessing Antibody Responses in Patients with Hypogammaglobulinaemia - Thon, Vojtěch (InTechOpen, 2012)
Computer modelling & simulation